2019
DOI: 10.1186/s40425-019-0807-6
|View full text |Cite
|
Sign up to set email alerts
|

Bi- and tri-valent T cell engagers deplete tumour-associated macrophages in cancer patient samples

Abstract: BackgroundTumour-associated macrophages (TAMs) are often implicated in cancer progression but can also exert anti-tumour activities. Selective eradication of cancer-promoting (M2-like) TAM subsets is a highly sought-after goal. Here, we have devised a novel strategy to achieve selective TAM depletion, involving the use of T cell engagers to direct endogenous T cell cytotoxicity towards specific M2-like TAMs. To avoid “on-target off-tumour” toxicities, we have explored localising expression of the T cell engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 52 publications
0
52
0
Order By: Relevance
“…We are also currently exploring the possibility of "arming" EnAd with different biologics to provide a two-, or in the case of combination with radiotherapy, three-pronged attack on the tumour microenvironment. In this way, armed EnAd viruses can target not only tumour cells [40], but also other tumour-promoting cells, such as fibroblasts [41] and M2-polarised, wound-healing macrophages [42] that form part of a tumour's support network. Though EnAd does not replicate in or lyse these latter cell types effectively, bi-and tri-specific T cell engagers encoded within the genome of EnAd can be secreted from infected tumour cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are also currently exploring the possibility of "arming" EnAd with different biologics to provide a two-, or in the case of combination with radiotherapy, three-pronged attack on the tumour microenvironment. In this way, armed EnAd viruses can target not only tumour cells [40], but also other tumour-promoting cells, such as fibroblasts [41] and M2-polarised, wound-healing macrophages [42] that form part of a tumour's support network. Though EnAd does not replicate in or lyse these latter cell types effectively, bi-and tri-specific T cell engagers encoded within the genome of EnAd can be secreted from infected tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…EnAd shows impressive selectivity for replication in human carcinoma cells from different types of cancers, including in a co-culture of cancer and normal cells in vitro [37], and has shown a promising targeting and safety profile in an early clinical trial [38]. EnAd can serve as an efficient vector for cancer-selective expression of immune-modulating biologics [39][40][41][42] and can be delivered via the bloodstream into the tumour following systemic administration to humans [43][44][45]. It is currently being tested in clinical trials against solid tumours in combination with several other treatment modalities [38,43].…”
Section: Introductionmentioning
confidence: 99%
“…3) [441], while trispecific antibodies, TriTEs and TriKEs , enhance therapeutic efficacy by providing additional costimulation through CD28, IL15R, or other activating receptors (Fig. 3) [442-444]. In terms of clinical development, BiTEs are more advanced and already in phase I clinical testing for lung cancer, for example, DLL3-directed for SCLC, and mesothelin-directed for NSCLC [445, 446], while TriTEs and TriKEs show promising preclinical results.…”
Section: Therapeutic Immunomodulationmentioning
confidence: 99%
“…In terms of clinical development, BiTEs are more advanced and already in phase I clinical testing for lung cancer, for example, DLL3-directed for SCLC, and mesothelin-directed for NSCLC [445, 446], while TriTEs and TriKEs show promising preclinical results. Another potential application of these products is the depletion of immunosuppressive cells in the TME, for example, M2 macrophages can be eliminated using CD206-directed BiTEs and TriTEs [444].…”
Section: Therapeutic Immunomodulationmentioning
confidence: 99%
“…In 2019, Scott et al developed both BiTE-and TriTE-armed Ad viruses and showed that they can be used to deplete tumor-associated macrophages in cancer patient samples [ 78 ]. BiTEs/TriTEs were designed to recognize CD3ε on T cells, along with CD206 or folate receptor β on M2-like macrophages.…”
Section: Bite- and Trite-armed Ovs Mediate Superior Therapeutic Efmentioning
confidence: 99%